Christian Education and Constructivism: Learning through the Adult Sunday School Class - Trammel Bristol; E. Paulette Isaac (Adult Education Research Conference, 2009)
Religious education has been the foundation of the Christian church. Sunday school has been an integral part of the teachings in the Christian church. However, little research exists, which examines adults’ learning in Sunday school classes. In this paper, we use the constructivist learning theory as a framework to examine learning experiences of adults in Sunday school.